Percutaneous thrombectomy for initial management of acute limb ischaemia - Araujo, Samuel T (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the safety and effectiveness of percutaneous thrombectomy for the initial management of acute limb ischaemia in adults.